INCREASING THE AWARENESS OF ARTICLES ABOUT THE IMPORTANCE OF USING OHS IN THE DEVELOPMENT OF PRODUCTION WAREHOUSES IN PENSARANAN VILLAGE - Kurniawan, I Wayan; Antari, Ni Putu Bayu Widhi (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
At present massive construction work is carried out in Indonesia. Construction work is a job that involves many things, so there is a risk of work accidents. The risk of work accidents must be minimal to improve the safety of the handyman when working. Therefore, there is an awareness of K3, which is still often overlooked. Many of the artisans consider that Personal Protective Equipment is only to meet the regulations. This also happened in the Construction of a Production Warehouse in Penyaringan Village. Increasing Artisan Awareness about the Importance of K3 is one of the solutions that can be done to build artisans to have awareness of the importance of using K3. The activities carried out are in the form of socialization and distribution of APD to artisans. This program will affect the level of awareness at work. When the handyman already has awareness and concern, it will reduce the risk of work accidents it has an impact on increasing productivity. After the activities are carried out, in working the handyman will pay more attention to K3 for the sake of a sense of security, comfort, and of course for his safety.